Multicenter Validation of the CamGFR Model for Estimated Glomerular Filtration Rate. Issue 4 (19th September 2019) - Williams, Edward H; Connell, Claire M; Weaver, James M J; Beh, Ian; Potts, Harry; Whitley, Cameron T; Bird, Nicholas; Al-Sayed, Tamer; Monaghan, Phillip J; Fehr, Martin; Cathomas, Richard; Bertelli, Gianfilippo; et al.
Abstract: Important oncological management decisions rely on kidney function assessed by serum creatinine–based estimated glomerular filtration rate (eGFR). However, no large-scale multicenter comparisons of methods to determine eGFR in patients with cancer are available. To compare the performance of formulas for eGFR based on routine clinical parameters and serum creatinine not calibrated with isotope dilution mass spectrometry, we studied 3620 patients with cancer and 166 without cancer who had their glomerular filtration rate (GFR) measured with an exogenous nuclear tracer at one of seven clinical centers. The mean measured GFR was 86 mL/min. Accuracy of all models was center dependent, reflecting intercenter variability of isotope dilution mass spectrometry–creatinine measurements. CamGFR was the most accurate model for eGFR (root-mean-squared error 17.3 mL/min) followed by the Chronic Kidney Disease Epidemiology Collaboration model (root-mean-squared error 18.2 mL/min).